2017
DOI: 10.5539/sar.v6n4p124
|View full text |Cite
|
Sign up to set email alerts
|

Screening Cover Crops for Weed Suppression in Conservation Agriculture

Abstract: The use of herbicides amongst smallholder farmers is minimal because herbicides are expensive and they require specialized application equipments. Weeds are problematic in conservation agriculture where herbicides are expensive for smallholder farmers. The use of cover crops can help to suppress weed growth and development by creating an environment which is not suitable for weeds survival. Cowpea (Vigna unguiculata (L.) Walp) dolichos lablab (Lablab purpureus L.) and velvet bean (Mucuna pruriens (L.) DC) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Bybee-Finley et al, (2017) found several negative relationships between crop species richness and weed biomass and crop biomass was found to be a more important factor than species richness for suppression of weeds. Phophi et al (2017) reported that, lablab and velvet bean (cover crop) had significantly lower weed species diversity at week 16 compared to the rest of the treatments, and also they found that, herbicide causes high weed species diversity. In this experiment it was observed that some species change under the influence of cover crop plants.…”
Section: Articlementioning
confidence: 98%
“…Bybee-Finley et al, (2017) found several negative relationships between crop species richness and weed biomass and crop biomass was found to be a more important factor than species richness for suppression of weeds. Phophi et al (2017) reported that, lablab and velvet bean (cover crop) had significantly lower weed species diversity at week 16 compared to the rest of the treatments, and also they found that, herbicide causes high weed species diversity. In this experiment it was observed that some species change under the influence of cover crop plants.…”
Section: Articlementioning
confidence: 98%
“…Known for its vigorous growth, cowpea is well-adapted to hot climatic conditions. However, herbicides did not exhibit effective weed suppression, largely attributed to suboptimal herbicide application methods (Mutondiwa et al, 2018) [40] .…”
Section: Crop Residue and Cover Cropsmentioning
confidence: 99%
“…In the developing world where soil infertility is high; it gives to the soil a huge supply of nitrogen and permits its cultivation without the use of nitrogenous fertilizer [5]. It also suppresses weeds and prevents soil erosion [6].…”
Section: Introductionmentioning
confidence: 99%